Trzeci sektor w Polsce i w krajach Europy Zachodniej : szanse i zagrożenia związane z przystąpieniem Polski do Unii Europejskiej - Olipra, Łukasz; Kowalska, Magdalena; Małek, Aleksandra (The Third Sector in Poland and in Western European Countries : Opportunities and Threats Associated with Poland's Joining the EU, 2005)
The non-governmental organizations sector is part of the national economy and as such manages capital and involves the workforce in its actions. The size of the Third Sector, as well as its value for the economy, are often significant which is connected with country's specificity and conditions created for the NGOs performance.The article presents the characteristics of the Third Sector in Poland against the background of the Third Sector in the Western Europe; it also points out the opportunities that stand before the Polish NGOs face, connected with Poland's accession to the European Union as well as the barriers that may hinder meeting these opportunities. In the conclusion, the authors quote the recommendations of the European Commission, the fulfillment of which shall enable the improvement of conditions for the actions of the non-governmental organizations in the European Member states.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 283-297